MIF and MMP-9 Serum Changes in Type II Diabetes and Non-Diabetic Subjects: A Short Communication - Alireza Rastgoo Haghi; Nasrin Khorami; Mahtab Fotoohi; Abbas Moradi (Iranian Society of Pathology, 2021)
Background & Objective: Diabetes is a metabolic disease and is associated with failure of various organs. Macrophage migration factor (MIF) and matrix metalloproteinase (MMP-9) are two of the most important factors in the pathogenesis of diabetes.Methods: In this descriptive-analytical study, 30 patients with type 2 diabetes mellitus from Hamadan Diabetes Center were selected by convenience sampling. Moreover, 30 healthy first-degree relatives and 30 unrelated non-diabetics, were examined for MMF and MMP-9 and their variations based on age, gender, body mass index (BMI) and hemoglobin A1C.Results & Conclusion: The mean and standard deviation of MIF in diabetic patients, and relatives and non-relatives of diabetic patients were 592.87±78.19, 131.82±88.27 and 94.63±23.88, respectively (P<0.001). The mean and standard deviation of the MMP-9 in diabetic patients, and relatives and non-relatives of diabetic patients were 2570.64±2220.03, 918.57±650.08 and 629.09±288.32, respectively (P<0.001). MIF and MMP-9 did not have a significant relationship with age, sex, duration of disease and BMI. However, we observed a direct and significant correlation between hemoglobin A1C and the level of MIF and MMP-9 (P<0.001). In patients with type 2 diabetes, serum levels of MMP-9 and MIF, consistent with HbA1c, increase with no significant association with age, sex, BMI and duration of diabetes.